Marriage and Women's Subalternity in the Ecranisation of Layla Majnun’s Story - Ahmad Syafa'at Junaidi; Suma Riella Rusdiarti (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThis article aimed to explain the textual changes in adapting Layla Majnun's story to the film Layla Majnun (2021). In addition, this article questioned the textual ideology of both works con-cerning marriage and women's subalternity.MethodThis article was qualitative research using the literature method. The corpus of this article were the novel Layla Majnun by Nizami Ganjavi and the film Layla Majnun (2021) by Monty Tiwa. This article used Linda Hutcheon's adaptation theory, the concept of subaltern initiated by Ga-yatri C. Spivak, and feminist concepts related to marriage.Results/FindingsThe results of this article show significant changes in the form of the adaptation of the story of Layla Majnun to the film. The changes are in the form of narrative structure, the meaning of mar-riage, and women's voices. The story of Layla Majnun focuses more on the storytelling of male characters, while the film focuses more on the storytelling of female characters.ConclusionThe textual shift from novel to film influences changes in the ideology of the text concerning mar-riage and women's subalternity. In the Layla Majnun novel, women are unable to speak out (subaltern) against repression from men concerning marriage. At the same time, the film Layla Majnun attempts to bring out women's voices to articulate their will in marriage.